The Effect of Perceived Ease of Use, Financial Literacy and Risk Perception on Interest in Using Mobile Banking: The Role of Trust as a Moderating Variable - Asyqar, Raki; Apriliza, Yafika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The rapid growth of digital technology has transformed the banking industry, including the adoption of mobile banking services in Indonesia. Although this trend shows improvement, some people are still reluctant to use it due to limited financial literacy, risk perception, and lack of trust. This study aims to analyze the influence of ease of use, financial literacy, and risk perception on interest in using mobile banking, and to examine the role of trust as a moderating variable. This study used a descriptive quantitative approach with 125 students from the Faculty of Economics and Business, University of North Sumatra as respondents. Data were collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) method with the assistance of SmartPLS 3.0 software. The results showed that ease of use and financial literacy had a positive and significant effect on interest in using mobile banking. However, risk perception did not show a significant effect. Furthermore, trust was not proven to significantly moderate the relationship between ease of use, financial literacy, and risk perception on interest in using mobile banking. These findings emphasize the importance of improving user convenience and financial literacy to encourage mobile banking adoption, while trust is not yet a strong enough moderating factor.